PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG SENAM HAMILTAHUN 2022 - Sri Siswati; Dina Indarsita; Juliandi (Poltekkes Kemenkes Medan, 2023)
Pregnant women are expected to have good health by knowing about pregnancy exercise (which is useful for facilitating the birthing process). Good quality of pregnant women's health will reduce maternal mortality. In the birth process there are three factors that cause prolonged labor, namely: energy, birth canal and fetus. One way to control problems such as energy problems is by doing pregnancy exercises. This type of research is descriptive analytical with a cross sectional study design. Sampling was carried out using total sampling, which is a sample determination technique when all members of the population are used as samples with a sample size of 40 people. The research period was April – September 2022. Data was collected from respondents using a questionnaire. The data analysis used was univariate (Frequency Distribution. The research results showed that there were 27 people (67.5%) pregnant women who had good knowledge about pregnancy exercise and there were 23 people (57.5%) pregnant women who had a positive attitude about pregnancy exercise. Conclusion: Description of knowledge and attitudes of pregnant women about pregnancy exercise, namely 67% and 57.5%. Suggestion: Health promotion at the Muliorejo Community Health Center, Deli Serdang Regency regarding pregnancy exercise is further improved with the hope that pregnant women will do pregnancy exercise at their respective homes so that the delivery was smooth.